Chronicles of the Divine Clock: A Comprehensive Analysis of Time Travel in the Quran - Dr. Hafsah Ayaz Qureshi; Ms. Syeda Ujala Zahid (jihat-ul-islam, 2023)
The Quran is the book of knowledge on various subjects including cosmological phenomena. The theory of relativity proposed by Albert Einstein changed the traditional physics concept of space and time travel and introduced a new dimension to the concept of time and space concerning the relative motion and gravitational field. The study uses a qualitative approach i.e. descriptive and analytical technique is used. The purpose of the research is to delve into the Quranic concept of time travel and analyse the narratives of prophet Uzair and Hazrat Solomon concerning the theory of relativity proposed by Albert Einstein. The primary data is collected from the Quran and e-books, articles, and scientific official websites are consulted to collect secondary data. The findings of the study showed that Quran provides a higher level of knowledge, related to scientific concepts that are far beyond human perception. The concept of time travel is discussed in the Quranic verse in the form of the story of Hazrat Uzair (A.S) and Hazrat Soloman (A.S) and Queen Sheba, which provides a concept of time travel that is beyond human intellect and is unable to achieve by the physicists.